Effect of Palm Kernel Meal Inclusion on Growth Performance, Immune and Visceral Organ Weights and Cecal Lactic Acid Bacteria in Neonatal Broilers - Martínez , Yordan; León, Aroldo Botello; Gebeyew, Kefyalew (International Journal of Poultry Science, 2020)
Background and Objective: Feed represents up to 70% of the total cost of production in the poultry industry; the challenge is to find alternative sources available to increase economic profitability. The study aimed to evaluate growth performance, immune and visceral organ weights and cecal lactic acid bacteria in neonatal broilers fed 5, 10 and 15% of palm kernel meal in the diet. Materials and Methods: Overall, 1,152 birds of the Ross 308® genetic line were used, randomly distributed in four treatments and six repetitions per treatment during the first 10 days old. Isoproteic and isoenergetic diets were made. Results: The dietary inclusion with 5 and 10% palm kernel meal increased (p<0.05) the final body weight compared to the control treatment and the latter level of inclusion improved (p<0.05) the feed conversion ratio. In addition, the greater contribution of fiber due to the higher inclusion of palm kernel increased the relative weight of the gizzard, however the relative weight of the small intestine decreased (p<0.05) with the dietary use of palm kernel, whereas the other indicators measured did not change (p>0.05) due to the effect of experimental diets. Likewise, palm kernel meal as an alternative feed in broiler diets increased the growth of cecal lactic acid bacteria, the green bacillus with white halo being the most representative. Conclusion: Palm kernel meal (5 and 15%) improved the performance, with a greater proliferation of cecal lactic acid bacteria and with few modifications in the relative weight of the digestive and immune organs.